Cenozoic geoclimatic changes and niche differentiation correlated with the diversification of the Gyrostemonaceae-Resedaceae-Forchhammeria-Tirania clade (Brassicales) - Ye-Ye Cao; Lian Lian; Huan-Wen Peng; Yuan-Yuan Ling; Kun-Li Xiang; Wei Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Tracing ¹⁵N dynamics reveals optimized nitrogen management with a novel plant-derived inhibitor in cropland soils - Ruiyuan Lian; Han Jiang; Jie Li; Huijie Lv; Jiafa Luo; Daijia Li; Xiaobing Hou; Shantong Li; Dongwei Li; Jingyuan Li; Kun Zhang (European Journal of Agronomy, 2026)

East Asian subtropical evergreen broadleaved forests act as a cradle for understory herbaceous diversity: A case study of Epimedium (Berberidaceae) - Lisi Hai; Huan-Wen Peng; Yuan-Yuan Ling; Xiao-Hong Chen; Xiao-Qian Li; Jun Zhang; Lian Lian; Kun-Li Xiang; Qiang Zhang; Hong-Hu Meng; Wei Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evaluation of the impact of biological inhibitors on nitrogen dynamics in different farmlands: Insights from controlled incubation experiments and field validation - Xiangyu Li; Han Jiang; Jie Li; Wei Wang; Dongwei Li; Jingyuan Li; Kun Zhang; Ruiyuan Lian; Daijia Li; Anran Long; Xiaobing Hou; Shantong Li (European Journal of Agronomy, 2026)

Catchment land use shapes lake-atmosphere thermal contrast and synchrony globally - Zhirong Yu; Gang Li; R. Iestyn Woolway; Jixiang Yang; Jiaming Hu; Juan Tao; Kun Shan; Kun Shi; Yunlin Zhang; Lian Feng; Erik Jeppesen; Qichao Zhou (Science Bulletin, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

Antimicrobial Peptide pBD2 Alleviates Intestinal Damage by Regulating MAPK and Nrf2 Signaling Pathway and Intestinal Microbiota in Mice Challenged with Enterotoxigenic Escherichia Coli K88 - Mingke Gu; Zhilong Du; Guixin Zhu; Shaoqiang Lian; Xiaoyang Shen; Kun Zhang; Hanfang Cai; Kejun Wang; Chunli Li (Probiotics and Antimicrobial Proteins, 2026)

Optimizing nitrogen use efficiency in maize with novel microencapsulated inhibitors: A 15N isotope tracer study - Dongwei Li; Jingyuan Li; Kun Zhang; Ruiyuan Lian; Han Jiang; Daijia Li; Shantong Li; Xiaobing Hou; Jie Li (Plant and Soil, 2026)

DNMT3a mediates FSTL3 methylation to regulate trophoblast proliferation, migration and invasion - Ning Wang; Xiujun Li; Yanyun Wang; Kun Wang; Ruixue Lian (Journal of Molecular Histology, 2026)

Microencapsulated nitrogen inhibitors promote ecosystem sustainability via greenhouse gas emission reduction and maize yield improvement - Kun Zhang; Ruiyuan Lian; Daijia Li; Jingyuan Li; Wenyu Wang; Dongwei Li; Yaqun Li; Kai Liu; Han Jiang; Xiaobing Hou; Shantong Li; Jian Gu; et al. (Agriculture, Ecosystems & Environment, 2026)

Unraveling the impact of diverse inhibitors on soil nitrogen emissions: the role of microbial community assembly across different soil types - Daijia LI; Kun ZHANG; Jie LI; Chunlin LI; Ruiyuan LIAN; Wei WANG; Jingyuan LI; Dongwei LI; Wenyu WANG; Yaqun LI; Kai LIU (Pedosphere, 2026)

Evaluation of the protective effects and mechanism of biochar on nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP) - Wenyu Wang; Kun Zhang; Jingyuan Li; Dongwei Li; Ruiyuan Lian; Daijia Li; Yaqun Li; Kai Liu; Jian Gu; Feilong Hu; Jie Li (Science of The Total Environment, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Complementary test of three-dimensional TROSE experiments for China advanced passive PWR under IVR strategy - Kun Han; Lian Chen; Zongyang Li; Huajian Chang; Fangfang Fang (Annals of Nuclear Energy, 2025)

Unraveling the dual-acting effects of 2-cyclopenten-1-one (CCO): Yield increase and gaseous emission mitigation via microbial regulation - Yaqun Li; Ruiyuan Lian; Wenyu Wang; Kun Zhang; Zhi Quan; Kai Liu; Jingyuan Li; Dongwei Li; Daijia Li; Lili Zhang; Jie Li (Soil and Tillage Research, 2025)

CAR19-T/NK cell and circular aptamer–drug conjugate (ApDC) combination treatment increases immunotherapy efficacy - Ling-Qi Kong; Su-Yun Chen; Xu Cui; Ya-Hui Hu; Lian Wang; Jia-Yao Zhu; Lan-Xuan Guan; Bing-Kun Wang; Li-Ting Yang; Kai-Ming Chen; Chao-Ming Zhou (Molecular and Cellular Biochemistry, 2025)

Codon usage bias analysis of self-incompatibility genes BrSRK, BrSLG, and BrSP11/BrSCR in Brassica rapa reveals insights into their coevolution - Yi-zhong Zhang; Min Ji; Lin-qiong Deng; Li-kun Lian; Li Jian; Rong-xian Zhang (Genetic Resources and Crop Evolution, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Karyotype and evolution trend analysis of seven diploid accessions and their autotetraploid lines of Tartary buckwheat native to China - Li-kun Lian; Pei Zhang; Xiao-fen Wu; Yi-zhong Zhang; Qing-fu Chen (Genetic Resources and Crop Evolution, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Assessing effect of toluene on immobilized denitrifying microorganisms: Enzyme activity, electronic behavior, and microbial community - Kun Wu; Chenxi Li; Nengsheng Liu; Liuzhou Chen; Yingjie Lian; Quanlin Zhao; Zhengfang Ye (Journal of Environmental Chemical Engineering, 2025)

Experimental investigation of 15.5-m prototype segment lining structures: The load equivalent method and in-situ verification - Li Zhang; Zhengzhou Lian; Kun Feng; Ruoyang Tang; Chuan He (Tunnelling and Underground Space Technology, 2025)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Notes on two new species of Russula subsect. Cyanoxanthinae (Russulaceae, Russulales) from southern China - Yan-Liu Chen; Jun-Feng Liang; Sheng-Kun Wang; Bin Chen; Jin-Hua Zhang; Meng-Ya An; Xing Li; Xue-Lian Gao; Xia Chen; Jin-Peng Liao (Mycological Progress, 2024)

Global Meta‐Analysis of Individual and Combined Nitrogen Inhibitors: Enhancing Plant Productivity and Reducing Environmental Losses - Wenyu Wang; Yaqun Li; Wei Wang; Keren Ding; Kun Zhang; Yulan Zhang; Kai Liu; Jingyuan Li; Dongwei Li; Ruiyuan Lian; Daijia Li; Jian Gu; et al. (Global Change Biology, 2024)
Nitrogen (N) transformation inhibitors have been widely recognized as a promising strategy to enhance crop productivity and mitigate N losses. However, the effectiveness of individual or combined inhibitors can vary significantly across different agroecosystems. Using meta‐analysis and cost–benefit analysis (CBA), we synthesized findings from 41 peer‐reviewed studies (285 observations) globally to evaluate the efficacy of urease inhibitors (UIs), nitrification inhibitors (NIs), and combined inhibitors (UINIs). We assessed their influence on soil inorganic N transformations, greenhouse gas emissions, and crop productivity across diverse climates, soil types, cropping systems, and fertilization practices. Our results indicated that combined UINIs were the most efficient, increasing crop yields by 5% and mitigating gaseous emissions by 51% compared to UIs or NIs alone. UINIs achieved these benefits by enhancing crop ammonium (NH 4 + ) availability through regulating urea hydrolysis and prolonging NH 4 + retention by suppressing nitrification in the soil. The CBA revealed that the overall economic benefits of UINIs application outweighed the costs, resulting in a net monetary benefit of $23.36 ha −1 , equivalent to a 6.4% increase in revenue. Both meta‐regression and random forest analyses suggested that UINIs performance was strongly influenced by factors such as N application rate, organic matter content, and soil pH. Notably, more substantial responses were observed in fine‐textured soils and/or crops exposed to high N fertilization rates. Acidic soils (pH 3 volatilization due to specific inhibitory interactions. In conclusion, these findings highlight UINIs beneficial impacts on crop productivity and environmental conservation, achieving a “win‐win” scenario by addressing various N‐loss challenges while enhancing economic outcomes. Further exploration and optimization of the interaction between climate, soil, plant, and management systems and the use of appropriate inhibitors are crucial for maximizing their positive impact on global climate and reaping corresponding economic benefits.

Elucidating the interaction mechanism of rice glutelin and soybean 11S globulin using multi-spectroscopy and molecular dynamics simulation methods - Peng-yu Zhu; Chun-min Ma; Yang Yang; Xin Bian; Li-kun Ren; Bing Wang; Xiao-fei Liu; Feng-lian Chen; Guang Zhang; Na Zhang (Food Chemistry, 2024)

Glowing and flaming autoignition of wood exposed to coupled convective and radiative heating - Junhui Gong; Hu Lin; Tong Cui; Haochen Lian; Lun Li; Kun Zhao (Fuel, 2024)

Genomic data and ecological niche modeling reveal an unusually slow rate of molecular evolution in the Cretaceous Eupteleaceae - Kun-Li Xiang; Sheng-Dan Wu; Lian Lian; Wen-Chuang He; Dan Peng; Huan-Wen Peng; Xiao-Ni Zhang; Hong-Lei Li; Jia-Yu Xue; Hong-Yan Shan; Gui-Xia Xu; Yang Liu; et al. (Science China Life Sciences, 2024)

FvDFR2 rather than FvDFR1 play key roles for anthocyanin synthesis in strawberry petioles - Xinyu Li; Xi Luo; Zhongchi Liu; Chong Wang; Anqi Lin; Kun Xiao; Minghao Cao; Junmiao Fan; Hongli Lian; Pengbo Xu (Plant Science, 2024)

Multistage and diverse melt-mantle interaction in dunite-harzburgite channel systems beneath oceanic slow-ultraslow spreading centers: Evidence from the Xigaze ophiolite (Tibet) - Li Wang; Qing Xiong; Jian-Ping Zheng; Hong-Kun Dai; Lian-Rong Tian; Xiang Zhou (Lithos, 2024)

Designing and preparing supramolecular encapsulation systems based on fraxetin and cyclodextrins for highly selective detection of nicotine - Yun-Han Yang; Zhen Zhang; Qiu-Lian Bao; Fang Zhao; Ming-Kun Yang; Xin Tao; Yan Chen; Jun-Tong Zhang; Li-Juan Yang (Carbohydrate Polymers, 2024)

Antibiotic resistance genes and heavy metals in landfill: A review - Yan-Jiao Li; Ying Yuan; Wen-Bing Tan; Bei-Dou Xi; Hui Wang; Kun-Long Hui; Jia-Bao Chen; Yi-Fan Zhang; Lian-Feng Wang; Ren-Fei Li (Journal of Hazardous Materials, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

The improvement of the oxidative oat (Avena sativa L.) protein based on ultrasound treatment: Study of structural, emulsifying, and rheological properties - Yue Xu; Yang Yang; Chun-min Ma; Xin Bian; Li-Kun Ren; Bao-xiang Liu; Lian-zhong Ai; Na Zhang (Food Hydrocolloids, 2023)

Biogeographic diversification of Actaea (Ranunculaceae): Insights into the historical assembly of deciduous broad-leaved forests in the Northern Hemisphere - Yuan-Yuan Ling; Kun-Li Xiang; Huan-Wen Peng; Andrey S. Erst; Lian Lian; Liang Zhao; Florian Jabbour; Wei Wang (Molecular Phylogenetics and Evolution, 2023)

Identification of Immune-Linked Hub Genes and Diagnostic Model Construction in Schizophrenia - Kun Lian; Zonglin Shen; Runxu Yang; Jing Ye; Binli Shang; Lei Dong; Hongfang Li; Jiabing Wu; Yuqi Cheng; Xiufeng Xu (Journal of Molecular Neuroscience, 2023)
Schizophrenia (SCZ) is a prevalent, severe, and persistent mental disorder with an unknown etiology. Growing evidence indicates that immunological dysfunction is vital in the development of SCZ. Our study aims to uncover potential immune-linked hub genes and immune infiltration characteristics of SCZ, as well as to develop a diagnostic model based on immune-linked central genes. GSE38484 and GSE54913 chip expression data for patients with SCZ and healthy controls were retrieved. Weighted gene co-expression network analysis (WGCNA) was performed to identify major module genes and critical immune-linked genes. Functional enrichment analysis was conducted to elucidate the involvement of key genes in the immunological response to SCZ, along with the examination of their protein interactions. Moreover, 202 peripheral blood samples were examined using the single-sample gene set enrichment analysis (ssGSEA) method to detect distinct immune cell types. Hub immune-linked genes in SCZ were identified using the minimal absolute contraction and selection operator analysis. Receptor profiles of central immune-linked genes were analyzed to distinguish the two groups. Finally, the association between immune-linked hub genes and various types of immune cells was assessed. Our findings revealed ten immune cell types and nine key genes involved in SCZ, including effector memory CD4+ T cells, activated CD8+ T cells, mast cells, naive CD8+ T cells, PBMC, type 17 helper cells (Th17), central memory CD8+ T cells, CD56 bright NK cells, memory B cells, and regulatory T cells. Diagnostic models constructed using LASSO regression exhibited an average area under the curve (AUC) of 0.866. Our results indicate immunological dysfunction as a factor in the development of SCZ. ASGR2 , ADRM1 , AHANK , S100A8 , FUCA1 , AKNA , GATA3 , AHCYL2 , and PTRH2 are the key regulatory genes of immune cells, highlighting their potential as novel therapeutic targets for SCZ.

Challenges and opportunities in animal models of psoriatic arthritis - Lin-Kun Bai; Ya-Zhen Su; Zong-Di Ning; Cheng-Qiang Zhang; Li-Yun Zhang; Gai-Lian Zhang (Inflammation Research, 2023)

Neiella litorisoli sp. nov., an alginate lyase: producing bacterium from South China Sea, and proposal of Echinimonadaceae fam. nov. in the order Alteromonadales - Jing-Ran Sun; Kun-Lian Mo; Xue Li; Yong-Hua Hu; Zhi-Yuan Liu; Hui-Qin Huang (Archives of Microbiology, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Effects on the intestinal morphology, inflammatory response and microflora in piglets challenged with enterotoxigenic Escherichia coli K88 - Kun Zhang; Xiaoyang Shen; Lu Han; Mengyun Wang; Shaoqiang Lian; Kejun Wang; Chunli Li (Research in Veterinary Science, 2023)

A complete genus-level phylogeny reveals the Cretaceous biogeographic diversification of the poppy family - Huan-Wen Peng; Kun-Li Xiang; Andrey S. Erst; Lian Lian; Rosa Del C. Ortiz; Florian Jabbour; Zhi-Duan Chen; Wei Wang (Molecular Phylogenetics and Evolution, 2023)

Ganoderma lucidum extract promotes tumor cell pyroptosis and inhibits metastasis in breast cancer - Chunlian Zhong; Yumei Li; Wulin Li; Shu lian; Ye Li; Changhui Wu; Kun Zhang; Guiyu Zhou; Weiyu Wang; Huo Xu; Mingqing Huang; Vladimir Katanaev; et al. (Food and Chemical Toxicology, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Decreased Plasma Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) Levels are Linked with Disease Severity in Patients with Liver Cirrhosis - Lian-Ying Yang; Ji-Ping Hou; En-Kun Han; Gang Qiao; Li-Bin Liu; Xue-Bo Men (International Journal of Peptide Research and Therapeutics, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Forest community assembly is driven by different strata‐dependent mechanisms along an elevational gradient - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Journal of Biogeography, 2019)
Aim The mechanisms driving forest community assembly along elevational gradients remain elusive. The distinct strata in heterogeneous forest are subject to differing assembly mechanisms. This study aims to evaluate how different ecological mechanisms driving forest community assembly across strata and spatial scales, and to identify how these assemblages respond to different abiotic or biotic variables along an elevational gradient. Location Yulong Mountain within Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We sampled plant species along a 1,200 m elevational gradient across forest strata (trees, shrubs and herbs) at different spatial scales (neighbourhood and community). We integrated phylogenetic and functional diversity to disentangle the roles of ecological mechanisms in structuring community assembly. We also determined the relative effects of climatic, soil and biotic variables and their interactions on these community assemblages. Results The phylogenetic and functional diversity of trees were lower at the extremes of the elevational gradient, where they were constrained by water availability or temperature. While communities with higher species diversity exhibited an overdispersed structure at mid‐elevations. For shrubs, overdispersion was exhibited at high elevations despite low species richness, which could be consistent with facilitative interactions or competition exclusion. However, most communities of herbs appear to have a markedly random structure, despite some incongruence between phylogenetic divergence and functional convergence, as well as influences from overstorey trees and local light conditions. The relative effects of abiotic variables on community structure were larger at the community scale than at the neighbourhood scale. Main conclusions Our study emphasises the importance of considering phylogenies and traits in understanding the strata‐ and scale‐dependent mechanisms of forest community assembly. Collectively, results indicate that contrasting assembly mechanisms interact across different strata along elevational gradients to shape diverse forest communities.

Greater than the sum of the parts: how the species composition in different forest strata influence ecosystem function - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Jia‐Yun Zou; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Ecology Letters, 2019)
The mechanisms underpinning forest biodiversity‐ecosystem function relationships remain unresolved. Yet, in heterogeneous forests, ecosystem function of different strata could be associated with traits or evolutionary relationships differently. Here, we integrate phylogenies and traits to evaluate the effects of elevational diversity on above‐ground biomass across forest strata and spatial scales. Community‐weighted means of height and leaf phosphorous concentration and functional diversity in specific leaf area exhibited positive correlations with tree biomass, suggesting that both positive selection effects and complementarity occur. However, high shrub biomass is associated with greater dissimilarity in seed mass and multidimensional trait space, while species richness or phylogenetic diversity is the most important predictor for herbaceous biomass, indicating that species complementarity is especially important for understory function. The strength of diversity‐biomass relationships increases at larger spatial scales. We conclude that strata‐ and scale‐ dependent assessments of community structure and function are needed to fully understand how biodiversity influences ecosystem function.

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Long non-coding RNA NEAT1 decreases the chemosensitivity of gastric cancer cells via regulating P-glycoprotein expression - Jian Wang; Qiong Niu; Ning Shi; Chengxia Liu; Haifeng Lian; Jiancheng Li; Kun Li (Molecular & Cellular Toxicology, 2017)

Organic two-photon nanoparticles modulate reactive oxygen species, intracellular calcium concentration, and mitochondrial membrane potential during apoptosis of human gastric carcinoma SGC-7901 cells - Geng Chen; Shou-Ying Li; Hamid Tayyab Malik; Yu-Guang Ma; Hong Xu; Lian-Kun Sun (Biotechnology Letters, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Jonesia luteola sp. nov., a bacterium isolated from Xinjiang Province, China - Yong Li; Yun-Jiao Zhang; Yong-Chun Ma; Zhi-Lian Gong; Man Jia; Fei Tian; Hans-Peter Klenk; Shu-Kun Tang (Antonie van Leeuwenhoek, 2015)

Assessment of association between the dopamine D2 receptor (DRD2) polymorphism and neurodevelopment of children exposed to lead - Lian Liu; Xijin Xu; Taofeek Akangbe Yekeen; Kun Lin; Weiqiu Li; Xia Huo (Environmental Science and Pollution Research, 2015)

The Role of the QseC Quorum-Sensing Sensor Kinase in Epinephrine-Enhanced Motility and Biofilm Formation by Escherichia coli - Kun Yang; Jun Meng; Yun-chao Huang; Lian-hua Ye; Guang-jian Li; Jie Huang; Hua-mei Chen (Cell Biochemistry and Biophysics, 2014)

The protective effect of rosmarinic acid on hyperthermia-induced C2C12 muscle cells damage - Kun-Lin Chen; Hui-Xia Li; Xing-Lian Xu; Guang-Hong Zhou (Molecular Biology Reports, 2014)

Requests for Health Education from Chinese Cancer Patients During Their Recovery Period: a Cross-Sectional Study - Wei-Li Qiu; Pei-Juan Lin; Fei-Qun Ruan; Xiao Wu; Miao-Ping Lin; Lian Liu; Jia-Yi Luo; Kun Lin (Journal of Cancer Education, 2013)

Four recombinant pluripotency transcriptional factors containing a protein transduction domain maintained the in vitro pluripotency of chicken embryonic stem cells - MiaoYing Yu; Song Lian; HongBing Han; Kun Yu; GuiGuan Li; ZhengXing Lian; Ning Li (Science China Life Sciences, 2013)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Potential inhibitors against Sclerotinia sclerotiorum, produced by the fungus Myrothecium sp. associated with the marine sponge Axinella sp. - Lian Wu Xie; Shu Mei Jiang; Hong Hui Zhu; Wei Sun; Yong Chang Ouyang; Shi Kun Dai; Xiang Li (European Journal of Plant Pathology, 2008)